Preliminary investigation on properties of novel sustainable composite : fish scales reinforced cement concrete - Arain, Fahad Ahmed; Jatoi, Masroor Ali; Raza, Muhammad Saleem; Shaikh, Fahad Ali; Khowaja, Farhan; Rai, Kunal (Penerbit Universiti Kebangsaan Malaysia, 2022)
This study focused on analysing the effect of fish scales reinforcement on fresh and hardened-state properties of concrete. For this purpose, 24 cubes and 24 cylinders were casted at a design mix ratio of 1:2.3:4.3. The water-cement ratio of 0.57 was maintained. The fish scales reinforcement levels of 0%, 1%, 1.5% and 2% by weight of cement were maintained for casting of specimens. For fresh-state assessment, the workability of concrete mixes was observed by slump test and the results showed that, with the addition of fish scales, the slump value decreased due to increase in water demand. With the addition of 2% Fish Scales, the workability of concrete mixes reduced by 36.40%. The compressive strength and tensile strength of concrete cubes and cylinders were tested with Universal Testing Machine (UTM) at curing period of 7 and 28 days. Out of 48 specimens casted, a total of 24 specimens were subjected to compressive strength test while other 24 specimens were tested for tensile strength. The results reported that with addition of 2% fish scales in concrete, the tensile strength of concrete increased but the compressive strength initially decreased and later increased. It can thus be concluded that the fish scales can be incorporated in concrete with steel to enhance the tensile strength of concrete. Keeping the initial decrease in compressive strength of concrete in consideration, it can be recommended that the fish scale reinforced concrete can be safely used in light weight structures and non-structural elements like floor slabs and ribs.